ChemInform Abstract: Visible Light Induced Cyclopropanation of Dibromomalonates with Alkenes via Double‐SET by Photoredox Catalysis. Issue 22 (15th May 2015) - Zhang, Yanbin; Qian, Rong; Zheng, Xingliang; Zeng, Yi; Sun, Jing; Chen, Yiyong; Ding, Aishun; Guo, Hao
Abstract: The green synthesis of cyclopropanes (III) is carried out under visible light or sunlight with similar high yields.